Web-based learning: a practical guide - Seamon, Mary Ploski (Published by Linworth Publishing, 2011)
Written by experienced technology trainers, this book is an easy-to-follow guide presenting a six-step, teacher-tested, sequential model, culminating in the completed design of a Web-based learning model. The handy "Technical Corners," interspersed throughout, give a quick overview of what skills are needed to develop or complete a Guided Tour, Scavenger Hunt, CyberInquiry or WebQuest. Sample projects are included in the "Exhibit Centers" of each chapter.